MARKETING MIX STRATEGY, MARKETING RELATIONSHIP STRATEGY, AND MARKETING PERFORMANCE: THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE - Juju, Undang; Supriadi, Tatang (Faculty of Economic and Business, University of Pasundan, 2024)
The purpose of this study is to determine the Effect of Marketing Mix Strategies and Marketing Relationship Strategies on Competitive Advantage and Its Implications for Marketing Performance Partially and Simultaneously. The method used in this study is a verifiative method with a quantitative approach. This research is a causal/verifiative research because it intends to determine the relationship between the above research variables with causal relationships so that there are independent variables (influencing variables) and dependent variables (influenced). comparative, associative and structural relationships (Path analysis, and Structural Equation Model / SEM relationships). The results of the study explained that simultaneously the positive influence of the variables of marketing mix strategy, and marketing relationship strategy on competitive advantage there are BUKU 2 Banks in West Java and DKI Jakarta Provinces. The biggest influence on competitive advantage comes from the Marketing Mix Strategy, while the smallest influence comes from the marketing relationship strategy. The Marketing Mix Strategy has a positive effect on the competitive advantage of BUKU 2 Bank in West Java and DKI Jakarta Provinces.